Can red cell distribution width in very low birth weight infants predict bronchopulmonary dysplasia?. Issue 3 (21st January 2022) - Oh, Seong Hee; Do, Hyun-Jeong; Park, Ji Sook; Cho, Jae Young; Park, Chan-Hoo
Abstract : Abstract: Red cell distribution width (RDW) is a useful marker for assessing the severity and prognosis of various diseases in adults. However, whether it is applicable to children, especially in newborns, has not been determined. This study aimed to investigate the RDW values of preterm infants and evaluate whether RDW values in the early days of life can predict bronchopulmonary dysplasia (BPD) development. One hundred and eight infants born at <30 weeks of gestation with a birth weight of <1500 g participated in this retrospective study. RDW values measured at birth, 7 days (D7), and 28 days (D28) after birth were reviewed. The changes in RDW values in the first month of life were analyzed, and we evaluated the relationship between RDW and BPD. The mean RDW values at birth, D7, D28 and the change from birth to D7 were 16.2 ± 0.1%, 17.5 ± 0.2%, 17.6 ± 0.2% and 1.3 ± 1.8%, respectively. RDW at birth was lower in the infants born at <28 weeks' gestational age than in those born at ≥28 weeks' gestational age (15.7 ± 0.3 vs 16.4 ± 0.2, P  = .024). RDW values of both groups increased during the first week after birth and did not differ significantly at D7. The levels remained similar at 1 month of age. RDW at birth, D7, and D28 and the changes in RDW from birth to D7 were not correlated with the development of BPD independent of its severity. The usefulness of RDW as a predictor of BPD development remains questionable and requires further study.